TEACHERS’ DIFFICULTIES IN IMPLEMENTING INDEPENDENT CURRICULUM AT SMA WAHYU MAKASSAR - Chitra Nurul Annisa Azis; Jusmaniar N; Muthmainnah Mursidin (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
This study aims to identify the difficulties faced by teachers in implementing the Independent Curriculum at SMA Wahyu Makassar. The research employed a descriptive qualitative study method. Qualitative data were collected through interviews, observations, and checklists involving second grade teachers as participants. The findings indicate that while the flexibility of the Independent Curriculum is appreciated for allowing adjustments to teaching methods and materials to meet student needs, several significant challenges were identified. Key difficulties include inadequate communication from the government regarding the curriculum, insufficient teacher preparation, and an overreliance on existing textbooks and guides. The lack of a clear vision and inconsistent support from various stakeholders further complicates the implementation process. Teachers expressed the need for a more defined vision and robust support systems, including ongoing professional development and improved infrastructure. Despite resistance to change and limited understanding of the curriculum's principles, stakeholder support and teacher commitment suggest that with appropriate adjustments, the Independent Curriculum can achieve its intended outcomes.